The communitarian revolutionary subject: new forms of social transformation. Issue 8 (2nd August 2020) - Barkin, David; Sánchez, Alejandra
Abstract: The hope for a unique revolutionary actor in the twentieth century evaporated as a result of the weaknesses of social organisations. This paper examines the potential of an almost-forgotten group of revolutionary actors – collectively organised and deliberately involved in processes of social and productive transformation with a legitimate claim to territory – whose present-day activities involve them in concerted processes to consolidate a different constellation of societies on the margins of the global capitalist system. Indigenous and peasant communities throughout the Americas are self-consciously restructuring their organisations and governance structures, taking control of territories they claimed for generations. They are also reorganising production to generate surplus, assembling their members to take advantage of underutilised resources and peoples' energies for improving their ability to raise living standards and assure environmental conservation and restoration. These communities are not operating in isolation. They coordinate activities, share information and build alliances. Hundreds of millions of people are participating in this growing movement; they occupy much more than one-quarter of the world's land area. There is great potential for others to join them, expanding from the substantial areas where they are already operational. Global social networks are ensuring that this dynamic accelerates.